Teachers’ Attitudes and Competencies as Catalysts for Inclusive Science Education: A Case Study of Public Elementary Schools in West Sumatra - Desri Sasmita; Elsa Efrina; Marlina; Damri (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines the contribution of teacher attitudes and competencies as catalysts for inclusive science education in public elementary schools in West Sumatra, Indonesia. Using a quantitative correlational design, data were collected from 190 teachers across 152 inclusive schools through validated Likert-scale questionnaires. Multiple linear regression analysis revealed that teacher attitudes and competencies together explain 60.0% of the variance in the implementation of inclusive education (R² = 0.600, F = 140.0, p < 0.001). Teacher competencies demonstrated a strong, significant partial effect (β = 0.725, p < 0.001), while attitudes showed a smaller but statistically significant contribution (β = 0.153, p = 0.035). All regression assumptions were met, confirming the model’s robustness. The findings underscore that while positive attitudes are necessary, professional competencies—particularly in pedagogical adaptation, collaboration, and inclusive assessment—are the dominant driver of effective inclusive practice. The study concludes that sustainable implementation of inclusive science education requires integrated professional development that simultaneously strengthens both attitudinal readiness and technical expertise.